Assessment of functional status and quality of life of students after acute respiratory viral diseases - Hnyp, I.Ya. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose : explore the functional status and quality of life of students after acute viral infectious diseases. Material : a total of 25 students aged 19-22 years after the acute respiratory viral infections and 20 healthy people. Results : It was found that the students observed a significant increase in heart rate at rest compared with healthy. Also deteriorates the functional state of the respiratory system. Overall performance of such students 60-80% lower than in healthy persons. Students after acute respiratory viral infections found increased tone autonomic nervous system. This impairs their function. Conclusions : after acute respiratory viral diseases in students the deterioration of the functional state. Significant deterioration in the quality of life of students is associated with reduced physical and social activity, peaking emotional problems.